The Meaning of Life of People with HIV - Dubu, Rima Gracia; Keraf, M. K. P. Abdi; Panis, Marleny Purnamasari (Journal of Health and Behavioral Science, 2025)
People Living with HIV (PLHIV) have complex challenges in terms of health, social, psychological, and spiritual aspects. Therefore, the meaning of life becomes one of the critical aspects in helping PLHIV to confront every challenge from various aspects of life, so that the author becomes interested in researching the description of the meaning of life in people with HIV. This study aims to determine the meaning of life among PLHIV in Kupang City. The research method employed a qualitative method with a phenomenological approach. The sampling technique used in this study employed a purposive sampling method, involving a total of 3 participants. The data collection technique in this study involved semi-structured interviews, utilizing Descriptive Phenomenological Analysis techniques. The results showed that all participants in this study could find meaning in their lives, as seen from aspects such as self-understanding, the meaning of life, changing attitudes, self-bonding, directed activities, and social support.